ENHANCING CRITICAL THINKING THROUGH ASSESSMENT - Mavlonova, Dildora (Журнал иностранных языков и лингвистики, 2021)
This article presents an overview about critical thinking providing definition from reliable sources. It also talks about the characteristics of an ideal critical thinker and the importance of critical thinking in language teaching. In addition, the issues are highlighted as why to teach critical thinking in the language classroom and how to enhance critical thinking through assessment.